Magical Capitalism Enchantment, Spells, and Occult Practices in Contemporary Economies (Springer International Publishing, 2018)
This volume of essays examines the ways in which magical practices are found in different aspects of contemporary capitalist societies. From contract law to science, by way of finance, business, marketing, advertising, cultural production, and the political economy in general, each chapter argues that the kind of magic studied by anthropologists in less developed societies - shamanism, sorcery, enchantment, the occult - is not only alive and well, but flourishing in the midst of so-called 'modernity'. Modern day magicians range from fashion designers and architects to Donald Trump and George Soros. Magical rites take place in the form of political summits, the transformation of products into brands through advertising campaigns, and the biannual fashion collections shown in New York, London, Milan and Paris. Magical language, in the form of magical spells, is used by everyone, from media to marketers and all others devoted to the art of 'spin'. While magic may appear to be opposed to systems of rational economic thought, Moeran and Malefyt highlight the ways it may in fact be an accomplice to it.